2003
DOI: 10.1161/01.hyp.0000078490.59735.6e
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Renin-Angiotensin System Increases Adiponectin Concentrations in Patients With Essential Hypertension

Abstract: Abstract-Adiponectin, an adipocyte-derived protein, has been suggested to play an important role in insulin sensitivity.We examined the association between insulin sensitivity (M value) evaluated by the euglycemic-hyperinsulinemic glucose clamp and adiponectin concentrations in 30 essential hypertensives (EHT) and 20 normotensives (NT) and investigated the effect of blockade of the renin-angiotensin system (RAS) on adiponectin concentrations. EHT were divided into 12 insulin-resistant EHT (EHT-R) and 18 non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
302
4
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(337 citation statements)
references
References 51 publications
22
302
4
9
Order By: Relevance
“…On the other hand, even after adjustment for differences in kidney function, serum ADPN remained elevated in patients with nephropathy compared with normoalbuminuric patients (Table 3). The study groups were also examined for differences in treatment with ACE inhibitors, because these drugs have been shown to increase serum ADPN in non-diabetic patients with essential hypertension [33], but as shown this did not explain our observations. Thus, there is evidence that mechanisms other than kidney function may be responsible for the higher serum ADPN levels in type 1 diabetic patients with nephropathy.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, even after adjustment for differences in kidney function, serum ADPN remained elevated in patients with nephropathy compared with normoalbuminuric patients (Table 3). The study groups were also examined for differences in treatment with ACE inhibitors, because these drugs have been shown to increase serum ADPN in non-diabetic patients with essential hypertension [33], but as shown this did not explain our observations. Thus, there is evidence that mechanisms other than kidney function may be responsible for the higher serum ADPN levels in type 1 diabetic patients with nephropathy.…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that RAS inhibitors 25,26 and CCBs 27 increase adiponectin levels in non-hemodialysis patients. Previous studies have shown that angiotensin II receptor blocker inhibits obesity-induced hypoadiponectinemia through the inhibition of reactive oxygen species generation in mice 28 and that some angiotensin II receptor blockers have peroxisome proliferator-activated receptor g-activating properties, 29 thereby stimulating adiponectin production.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al 20 also investigated the effect of the RAS blockade and did not find any effect on adiponectin levels. However, several investigators reported that angiotensin-converting enzyme inhibitor, angiotensin II receptor blocker 25,26 and CCB 27 increase adiponectin levels in non-hemodialysis patients. Thus, we speculated that these drugs might also increase adiponectin levels in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have explored the relationship between angiotensin II, the renin-angiotensin system and its blockade and adiponectin. [13][14][15][16][17] One study 13 in rats measured changes in plasma adiponectin levels following angiotensin II infusion and found that angiotensin II infusion decreased plasma adiponectin levels via the angiotensin II type I receptors, resulting in impaired insulin sensitivity.…”
mentioning
confidence: 99%
“…Table 1 summarizes the findings of these studies. Furuhashi et al 14 reported a significant increase in adiponectin levels Nifedipine therapy improved platelet activation markers, micro particles and adiponectin levels in hypertensive patients with type II diabetes Six-month nifedipine therapy reduced blood pressure, with a significant rise in adiponectin levels in subjects with type II diabetes (Po0.01) Nifedipine has possible beneficial antiatherosclerotic effects in addition to its antihypertensive action Significant fall in the baseline high levels of procoagulant markers (platelet-and monocytederived microparticles) in hypertensives with diabetes with nifedipine therapy Abbreviations: ACE-I, angiotensin-converting enzyme inhibitor; ARB, angiotensin receptor blocker; RAS, renin-angiotensin system.…”
mentioning
confidence: 99%